Terpene and resin acid contents in Scots pine stem lesions colonized by the rust fungus Cronartium pini - Kaitera, Juha; Piispanen, Juha; Bergmann, Ulrich (Wiley-Blackwell, 2021)
Cronartium pini causes economic losses especially on Scots pine in northern Europe. Scots pine reacts to rust infection by resin flow. The chemicals enriched in wood after Cronartium infection have not been investigated before. We investigated resin acids and mono- and sesquiterpenes produced in Cronartium-infected wood. Cronartium-infected wood was extracted with acetone, and the extractives were analysed by GC-mass spectrometry (GC-MS) and compared to those from control wood. Among resin acids, abietic acid, levopimaric acid, palustric acid, dehydroabietic acid and neoabietic acid were the richest (32–68 mg/g) in Cronartium-infected wood. Among monoterpenes, concentration of α-pinene was the highest (49 mg/g) in Cronartium-infected wood. Concentrations of all monoterpenes and resin acids and most sesquiterpenes were significantly higher (1.3- to 108-fold) in Cronartium-infected wood compared to control wood. In the control wood, the extractive content was greater (1.1- to 14-fold) than in the literature suggesting that the chemical processes were strongly affected by the rust. The results suggest that terpenes and resin acids are produced by the host to protect it from Cronartium rust.
Keywords: forest pathology; tervasroso; terpenes; resin acids; lesions; Pinus sylvestris; rust disease; secondary chemicals; wood chemistry; gas chromatography–mass spectrometry